2018
DOI: 10.1523/jneurosci.3618-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Synapse Remodeling Following Astrocyte-Specific Regulation of Ephrin-B1 in the Adult Hippocampus

Abstract: Astrocyte-derived factors can control synapse formation and functions, making astrocytes an attractive target for regulating neuronal circuits and associated behaviors. Abnormal astrocyte-neuronal interactions are also implicated in neurodevelopmental disorders and neurodegenerative diseases associated with impaired learning and memory. However, little is known about astrocyte-mediated mechanisms that regulate learning and memory. Here, we propose astrocytic ephrin-B1 as a regulator of synaptogenesis in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 72 publications
4
51
0
Order By: Relevance
“…There were no detectable changes in ephrin-B1 levels in astrocytes or neurons of TAM-injected WT mice (not shown). In TAM-treated KO mice, ephrin-B1 immunoreactivity was observed only in neuronal cell bodies and dendrites of the CA1 hippocampus, but was significantly reduced in hippocampal astrocytes as previously reported (Nikolakopoulou et al, 2016;Koeppen et al, 2018). Genotypes were confirmed by PCR analysis of genomic DNA isolated from mouse tails.…”
Section: Micesupporting
confidence: 75%
See 1 more Smart Citation
“…There were no detectable changes in ephrin-B1 levels in astrocytes or neurons of TAM-injected WT mice (not shown). In TAM-treated KO mice, ephrin-B1 immunoreactivity was observed only in neuronal cell bodies and dendrites of the CA1 hippocampus, but was significantly reduced in hippocampal astrocytes as previously reported (Nikolakopoulou et al, 2016;Koeppen et al, 2018). Genotypes were confirmed by PCR analysis of genomic DNA isolated from mouse tails.…”
Section: Micesupporting
confidence: 75%
“…However, little is known about the role of astrocytic ephrin-B1. We previously reported that deletion and overexpression (OE) of astrocytic ephrin-B1 in the adult CA1 hippocampus affects contextual memory (Koeppen et al, 2018), but the mechanism is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The Eph tyrosine kinase receptors were subdivided into 9 EPHA receptors (EPHA1-8 and EPHA10) and 5 EPHB receptors (EPHB1-4 and EPHB6), based on their binding to two subclasses of cognate ligands, Ephrin-As and Ephrin-Bs (Dines and Lamprecht, 2016;Taylor et al, 2017). The EPHB/Ephrin-Bs, which are distributed extensively and provide unique bidirectional signaling between neurons and astrocytes, have attracted considerable attention because of their regulation of neuronal maturation and synaptic plasticity (Koeppen et al, 2018). Dysfunction of EPHB2 and its ligand EFNB1 has been implicated in brain disorders, such as cognition disorders and depression (Zhang et al, 2016;Koeppen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The EPHB/Ephrin-Bs, which are distributed extensively and provide unique bidirectional signaling between neurons and astrocytes, have attracted considerable attention because of their regulation of neuronal maturation and synaptic plasticity (Koeppen et al, 2018). Dysfunction of EPHB2 and its ligand EFNB1 has been implicated in brain disorders, such as cognition disorders and depression (Zhang et al, 2016;Koeppen et al, 2018). Even in other subtypes of depression animal models, EPHB2 was preliminarily found to regulate neuronal development, NMDAR function, and synaptic plasticity of the hippocampus and PFC (Zhang et al, 2016;Zhen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SPARCL1, thrombospondin-1, Chordin-like 1, TGFβ, and glypicans), the molecular mechanisms utilized by astrocytes to instruct synapse formation and to regulate synapse function are largely unknown (Allen et al, 2012;Blanco-Suarez et al, 2018;Christopherson et al, 2005;Diniz et al, 2012;Kucukdereli et al, 2011;Nagal et al, 2019). Recent studies have implicated cell-adhesion molecules expressed by astrocytes, such as neuroligins and Ephrin-B1, in regulating synapse formation (Koeppen et al, 2018;Stogsdill et al, 2019). However, the extent to which astrocytes employ these or other cell adhesion molecules to regulate synaptic information processing remains unclear (Bohmback et al, 2018;Durkee et al, 2019;Farhy-Tsenlnicker et al, 2018;Papouin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%